# Find the sum and product of roots of under root 3X ^2 _under root 6x_3 = 0

2
by sofiya
Give me a min
OKAY
Can u answer my fewmore questions
If x_3 is a common factor of x^2_ x+p=0 and x^2 + X +q=0 then find p:q
Put x=3 in both the equations we get p= -6 and q= -12 then p:q = -6/-12 = 1/2 answer

2015-01-15T11:04:41+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
✔️3x^2 -✔️6x-3=0 comparing it with ax^2 + bx +c =0 we get a= ✔️3 , b = -✔️6 and c= -3 now sum of roots = -b/a = ✔️6/✔️3 =✔️2 and product of roots = c/a = -3/✔️3 = -✔️3 answer
2015-01-15T12:19:31+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
So for the quadratic equation ax² + bx + c = 0

sum of roots , s = -b/a

product of the roots, p = c/a

so for the equation

we have a = √3 ,  b = - √6 , c = - 3

so s = √2

and p = -√3